ANALISIS YURIDIS REGULASI PEMAKAIAN SEPEDA MOTOR UNTUK MENGANGKUT PENUMPANG PADA MASA PANDEMI CORONA VIRUS DISEASE 2019 - Masitha, Fachriah Dewi; Hikmah, Nurul; Sulistyowati, Eny (Universitas Negeri Surabaya)
2019 was the beginning for Indonesia to experience a Covid-19 pandemic, The existence of covid -19 has led to various regulations related to preventing the spread of the pandemic. Large-scale Social Restrictions (PSBB) and New Normal Life are a form of order in the transportation sector for two-wheeled vehicles or motorbikes to carry passengers during the covid-19 pandemic. However, the provisions in the sector found a problems. Namely the existence of a conflict of norms contained in Permenhub Nu. 18 of 2020 with Permenhub Nu, 12 of 2019. The Focus of this research is the provions written in article 2 of Permenhub Nu. 12 of 2019 and article 11 paragraph (1) Permenhub Nu, 18 of 2020. The results showed that there was a conflict between the article 2 Permenhub Nu. 12 of 2019 with article 11 paragraph (1) Permenhub Nu. 18 of 2020 which wil have legas consequences for motorcyclist for the benefit of the community. Conflict of norms between Permenhub Nu. 18 of 2020 with Permenhub Nu. 12 of 2019 refers to the 3 principle of legal objectives, so that the result is that Permenhub Nu. 18 of 2020 and Permenhub Nu. 12 of 2019 has not provided a legal certainty for motorbike users for the benefit of the community during the covid-19 pandemic, due to the law with the enactment of Permenhub Nu. 18 of 2020 and Permenhub Nu. 12 of 2019 exist in both public and private spheres. Keywords: covid-19, legal consequences, legal certainty.